Strategy for Packaging Political Content on The Saeful Zaman Youtube Channel - Herlina, Rita; Simabur, Lisda Ariani; Ningsih, Fuji Fera Rahayu; Darmawan, Andri (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2023)
Many political events that Saeful Zaman Channel can discuss and criticize daily are the background of this research with the theme